Exploring the Moderating Effect of Quality Management Practices towards Supply Chain Performance in Malaysia Automotive Industry - Abdul Aziz Othman; Mohamad Ghozali Hassan; Mohd Azril Ismail; Kamal Imran Mohd Sharif (International Journal of Supply Chain Management, 2016)
This article reports a study designed to explore the state of supply chain management in the Malaysian automotive industry by examining the moderating effect of quality management practices towards the relationship between supply chain strategy and supply chain performance. This study is accomplished by using survey questionnaire that was answered by 65 respondents from Malaysian automotive components manufacturing firms. This study used the SPSS tool to test the hypotheses. The study found that quality management practices act as a quasi moderator towards relationship between supply chain strategy and supply chain performance. This study also empirically proved that for highly quality management practices, it can be as a strategy for improvement of supply chain performance. Implications of the finding are further elaborated.